Pain experiences and effectiveness of pain management after cesarean section in postpartum mothers at Hue University of Medicine and Pharmacy Hospital - Pham, Thi Tinh; Le, Thi Huong Van; Nguyen, Thi Nguyet; Ho, Thi Thuy Trang; Nguyen, Thi Anh Phuong; Ton, Nu Minh Duc (Tạp chí Y Dược Huế, 2025)
Background: Pain following a cesarean section can hinder a mother’s recovery after childbirth, disrupt the mother-child bond, negatively impact the mother’s mental well-being, and hamper breastfeeding. The accurate assessment of pain levels and the proper use of pain relief methods can significantly improve the physical and mental health of mothers and babies. This support can aid in quick recovery after a cesarean section, create optimal conditions for mother-child bonding, and help develop future childcare skills. Objectives: 1) To describe pain experiences and effectiveness of pain management after cesarean section in postpartum mothers at the Obstetrics and Gynecology Department, Hue University of Medicine and Pharmacy Hospital; 2) To identify factors related to pain experiences after cesarean section in postpartum mothers. Subject and methods: Cross-sectional study design among 190 postpartum mothers after cesarean section on the 2nd day at the Obstetrics and Gynecology Department, Hue University of Medicine and Pharmacy Hospital from August 2021 to July 2022. Results: The average pain level of the study group was 5.98 ± 0.923/10. The percentage of postpartum mothers with moderate to severe pain at the time of the most pain was 95.2%. The pain relief method used was first-class analgesics, and the average pain relief level was 5. 47 ± 1.435/10. The study found a statistically significant association between pain experiences after cesarean section and the following factors: age, pregnancy status, number of births, prenatal complications, prenatal anxiety, number of cesarean sections, family support, and types of anesthesia (p < 0.05). Conclusion: The rate of postpartum mothers experiencing moderate to severe pain after a cesarean section is quite high. However, the effectiveness of postoperative pain management in postpartum mothers is still very low. More effective pain management methods should be applied, especially for individuals with risk factors that increase their pain experiences, to improve the effectiveness of postpartum care and treatment.